Adsorption of Biebrich Scarlet Dye into Remains Chromium and Vegetable Tanned Leather as Adsorbents - AL-Shammari, Noor Hussein; AL-Mammar, Dunya Edan (Iraqi Journal of Science, 2022)
Chromium tanned leather wastes (CTLW) and vegetable tanned leather wastes (VTLW) were used as adsorbent materials to remove the Biebrich scarlet dye (BS), as an anionic dye from wastewater, using an adsorption method. The effects of various factors, such as weight of leather waste, time of shaking, and the starting concentration of Biebrich scarlet dye, temperature and pH were studied. It described the adsorption process using Langmuir and Freundlich isotherm models. The obtained results agreed well with the Langmuir model, and the maximum adsorption capacities of CTLW and VTLW were 73.5294 and 78.1250 mg.g⁻¹, respectively, suggesting a monolayer adsorption process. The adsorption kinetic was found to follow a pseudo-second-order kinetic model with correlation coefficients R2 > 0.9982 and 0.9900 for CTLW and VTLW, respectively. The results predicted that chromium leather wastes were more suitable adsorbents for the removal of BS dye from wastewater than vegetable tanned leather wastes, and the adsorption process is endothermic, according to the study of the effect of temperature.